Minimalistic supramolecular proteoglycan mimics by co-assembly of aromatic peptide and carbohydrate amphiphiles. Issue 8 (9th January 2019) - Brito, Alexandra; Abul-Haija, Yousef M.; da Costa, Diana Soares; Novoa-Carballal, Ramon; Reis, Rui L.; Ulijn, Rein V.; Pires, Ricardo A.; Pashkuleva, Iva
Abstract : A modular two-component supramolecular hydrogel composed of a peptide core and carbohydrate shell as a minimalistic mimic of proteoglycans. Abstract : We report the co-assembly of aromatic carbohydrate and dipeptide amphiphiles under physiological conditions as a strategy to generate minimalistic proteoglycan mimics. The resulting nanofibers present a structural, fluorenylmethoxycarbonyl-diphenylalanine (Fmoc-FF) core and a functional carbohydrate (Fmoc-glucosamine-6-sulfate or -phosphate) shell. The size, degree of bundling and mechanical properties of the assembled structures depend on the chemical nature of the carbohydrate amphiphile used. In cell culture medium, these nanofibers can further organize into supramolecular hydrogels. We demonstrate that, similar to proteoglycans, the assembled gels prolong the stability of growth factors and preserve the viability of cultured cells. Our results demonstrate that this approach can be applied to the design of extracellular matrix (ECM) substitutes for future regenerative therapies.